A new combined braking approach of magnetorheological fluids brake based on fuzzy controller and improved PID controller. (December 2021) - Hua, Dezheng; Liu, Xinhua; Gupta, Munish Kumar; Fracz, Pawel; Li, Zhixiong
With the aim to improve working performance of magnetorheological fluids (MRF) brake, a combined braking approach is proposed in this paper. A data acquisition system of MRF brake is designed and transfer function is identiﬁed for the device. Furthermore, based on the excitation current-extrusion pressure combined braking system, a fuzzy controller is designed to distribute the target torque. Moreover, through integration of fruit fly optimization algorithm (FOA) and particle swarm optimization algorithm (PSOA), an improved proportional-integral-differential (PID) controller is presented to conduct braking mechanism. Finally, the simulations and experiments are carried out. The results show that the combined braking approach with fuzzy controller and improved PID controller has characteristics of quick response and no overshoot, and superior to conventional PID and FOA PID controller.